Jahez (Ready) - Climate-ready refugee hosting communities in Jordan: stakeholder consultation meeting on climate and weather information landscape analysis - Norwood-Brown, L.; Ticehurst, H.; El Hajj, R.; Stone, Jeremy; Masoud, Ahmed (International Water Management Institute, 2025)
The “Jahez (Ready) - Climate-ready refugee hosting communities in Jordan” project held its first consultation meeting on climate and weather information on 20 May 2025 in Amman, Jordan. The meeting aimed to gather practical insights to enrich the understanding of weather and climate information systems in Jordan focusing on the three Jahez pilot sites in Al-Azraq, Al-Ramtha, and Irbid municipalities. The meeting brought together 21 key individuals, including representatives from the UK’s Foreign, Commonwealth & Development Office (FCDO), target municipalities, and key government entities such as the Ministry of Environment (MoEnv), Ministry of Agriculture (MoA), Ministry of Local Administration, the Jordan Meteorological Department (JMD), the National Center for Security and Crisis Management (NCSCM), and the Cities and Villages Development Bank (CVDB). Active development partners were also present including Mercy Corps and the World Food Programme (WFP).